Review Of Physical Health Knowledge Of Integrated Islamic Middle School Student Riyadhul Ulum - Muhammad Amrul Iqsan; Siska b; debby Indah; Arisman r (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
Physical health is a condition when a person's body is healthy and fit, and their organs and body systems function properly. Physical health is also known as physical fitness. The physical health of students at Riyadhul Ulum Integrated Islamic Middle School, Ujung Batu District, Rokan Hulu Regency, is often disturbed, including hair health, eye health, nose health, ear health, dental and oral health, nail health, and skin health. The purpose of this study was to find out about students' physical health knowledge. This type of research is quantitative descriptive. The population in this study amounted to 108 people. The sample in this study amounted to 58 people using the purposive sampling technique. Data collection was carried out using a research sample questionnaire. The data obtained were analyzed using the descriptive percentage analysis formula (%). The results of the study showed that the implementation of physical health knowledge of students of Riyadhul Ulum Integrated Islamic Middle School, Ujung Batu District, Rokan Hulu Regency, was in the